PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH PROBLEM BASED LEARNING (PBL) PADA PELAJARAN BAHASA INDONESIA GUNA MENINGKATKAN TERAMPIL MEMBACA DAN MENULIS LANJUT DI KELAS IV SEKOLAH DASAR - Nurhayati, Nurhayati; Mardiana, Nana; Rianti, Rianti (STKIP Setiabudhi, 2021)
This study contains the application of a problem based learning model that aims to improve theunderstanding and learning outcomes of fourth grade elementary school students. What is faced in thislearning is that the lessons taught by the teacher still use conventional methods, namely the lecturemethod, this learning process is only teacher-centered and without involving students so that it does notattract students' interest and motivation to learn and students become less active in participating inlearning activities. The problem based learning model is useful for improving students' understandingand learning outcomes in the learning process so that learning objectives can be achieved. The methodused in this research is the best practice method. Data collection techniques used in this study were tests,observations, interviews, documentation and field notes. It can be concluded that the application of theProblem Based Learning (PBL) problem-based learning model in Indonesian lessons is to improveadvanced reading and writing skills in grade IV Elementary School.Keywords: Problem Based Learning (PBL), Reading and Writing SkillsAbstrakPenelitian ini berisi tentang penerapan model problem based learning yang bertujuan untukmeningkatkan pemahaman dan hasil belajar siswa kelas IV Sekolah Dasar. Yang dihadapi padapembelajaran ini adalah pelajaran yang disaikan oleh guru masih menggunakan metode konvensionalyaitu metode ceramah, proses pembelajaran ini hanya berpusat pada guru dan tanpa melibatkan siswasehingga kurang menarik minat dan motivasi siswa untuk belajardan siswa menjadi kurang aktif dalammengikuti kegiatan pembelajaran. Model problem based learning berguna untuk meningkatkanpemahaman dan hasil belajar siswa dalam proses pembelajaran sehingga tujuan pembelajaran dapattercapai. Metode yang digunakan dalam penelitian ini adalah metode best practice. Teknik pengumpulandata yang digunakan dalam penelitian ini adalah tes, observasi, wawancara, dokumentasi dan catatanlapangan. Dapat disimpulkan bahwa Penerapan model pembelajaran berbasis masalah Problem BasedLearning (PBL) pada pelajaran Bahasa Indonesia guna meningkatkan terampil membaca dan menulislanjut di kelas IV Sekolah Dasar.Kata kunci: Problem Based Learning (PBL), Keterampilan Membaca dan Menulis